Metamaterial-inspired antenna array for application in microwave breast imaging systems for tumor detection - Alibakhshikenari, Mohammad; Virdee, Bal Singh; Shukla, Pancham; Parchin, Naser Ojaroudi; Azpilicueta, Leyre; See, Chan; Abd-Alhameed, Raed; Falcone, Francisco; Huynen, Isabelle; Denidni, Tayeb A.; Limiti, Ernesto (IEEE, 2020)
This paper presents a study of a planar antenna-array inspired by the metamaterial concept where the resonant elements have sub-wavelength dimensions for application in microwave medical imaging systems for detecting tumors in biological tissues. The proposed antenna consists of square-shaped concentric-rings which are connected to a central patch through a common feedline. The array structure comprises several antennas that are arranged to surround the sample breast model. One antenna at a time in the array is used in transmission-mode while others are in receive-mode. The antenna array operates over 2-12 GHz amply covering the frequency range of existing microwave imaging systems. Measured results show that compared to a standard patch antenna array the proposed array with identical dimensions exhibits an average radiation gain and efficiency improvement of 4.8 dBi and 18%, respectively. The average reflection-coefficient of the array over its operating range is better than S11 ≤ −20 dB making it highly receptive to weak signals and minimizing the distortion encountered with the transmission of short duration pulse-trains. Moreover, the proposed antenna-array exhibits high-isolation on average of 30dB between radiators. This means that antennas in the array (i) can be closely spaced to accommodate more radiators to achieve higher-resolution imaging scans, and (ii) the imagining scans can be done over a wider frequency range to ascertain better contrast in electrical parameters between malignant tumor-tissue and the surrounding normal breast-tissue to facilitate the detection of breast-tumor. It is found that short wavelength gives better resolution. In this experimental study a standard biomedical breast model that mimics a real-human breast in terms of dielectric and optical properties was used to demonstrate the viability of the proposed antenna over a standard patch antenna in the detection and the localization of tumor. These results are encouraging for clinical trials and further refinement of the antenna-array.